Factors associated with HIV-positive status awareness among adults with long term HIV infection in four countries in the East and Southern Africa region: A multilevel approach. - Bongi Siyabonga Nkambule; Grace Sambo; Halide Z Aydin; Nadire Gülçin Yildiz; Kemal Aydin; Hatice Yildiz; Ichtiarini Nurullita Santri; Yuniar Wardani; Khoiriyah Isni; Bwanalori Mwamlima; Yohane Vincent Abero Phiri (Public Library of Science (PLoS), 2023)
Antiretroviral treatment (ART) appropriately and regularly used decreases the human immunodeficiency virus (HIV) viral load in the bloodstream, preventing HIV-infected people from spreading the infection to others. Disparities in ART adoption persists in East and Southern Africa, with low HIV-positive status knowledge being the primary factor. We investigated individual and household characteristics of HIV-positive status awareness among adults with long-term HIV infection in four East and Southern African countries: Eswatini, Malawi, Tanzania, and Zimbabwe. The study analyzed data from surveys conducted in Eswatini, Malawi, Tanzania, and Zimbabwe in 2015-2016. Only individuals who tested positive for HIV through rapid tests were included in the analysis. Those who already knew they were HIV-positive were categorized as aware, while those who reported being negative, never tested, or didn't know their status were categorized as unaware. Statistical models were used to examine various factors related to HIV awareness. Pooled and country-specific odds ratios were computed. The percentage of people who knew they had HIV ranged from 58% (Tanzania and Malawi) to 87% (Eswatini). After adjusting for other variables, young persons in all countries were less likely to be aware of their HIV-positive status. Gender, marital status, education, working status, household wealth, and urbanization level of households were also associated with HIV-positive status awareness but inconsistent across countries. HIV-positive status awareness in these four East and Southern African nations remained unsatisfactory as compared to the United Nations' 95% guideline, indicating that testing and knowledge of HIV testing in this region still has a lot of potential for improvement. The observed variations among nations may be attributable to differences in HIV pandemic culture and policies. The findings of this study will assist governments determining which subpopulations to target to boost adoption of HIV testing services, as well as in designing and development of policies.